Synovial tissue hypoxia and inflammation in vivo. Issue 7 (3rd May 2010) - Ng, C T; Biniecka, M; Kennedy, A; McCormick, J; FitzGerald, O; Bresnihan, B; Buggy, D; Taylor, C T; O'Sullivan, J; Fearon, U; Veale, D J
Abstract : Introduction: Hypoxia is a microenvironmental feature in the inflamed joint, which promotes survival advantage for cells. The aim of this study was to examine the relationship of partial oxygen pressure in the synovial tissue (tPO2 ) in patients with inflammatory arthritis with macroscopic/microscopic inflammation and local levels of proinflammatory mediators. Methods: Patients with inflammatory arthritis underwent full clinical assessment and video arthroscopy to quantify macroscopic synovitis and measure synovial tPO2 under direct visualisation. Cell specific markers (CD3 (T cells), CD68 (macrophages), Ki67 (cell proliferation) and terminal deoxynucleotidyl transferase dUTP nick end labelling (cell apoptosis)) were quantified by immunohistology. In vitro migration was assessed in primary and normal synoviocytes (synovial fibroblast cells (SFCs)) using a wound repair scratch assay. Levels of tumour necrosis factor α (TNFα), interleukin 1β (IL1β), interferon γ (IFNγ), IL6, macrophage inflammatory protein 3α (MIP3α) and IL8 were quantified, in matched serum and synovial fluid, by multiplex cytokine assay and ELISA. Results: The tPO2 was 22.5 (range 3.2–54.1) mm Hg and correlated inversely with macroscopic synovitis (r=−0.421, p=0.02), sublining CD3 cells (−0.611, p<0.01) and sublining CD68 cells (r=−0.615, p<0.001). No relationship with cell proliferation or apoptosis was found. Primary and normal SFCs exposed to 1% and 3% oxygen (reflecting the median tPO2 in vivo) induced cell migration. This was coupled with significantly higher levels of synovial fluid tumour necrosis factor α (TNFα), IL1β, IFNγ and MIP3α in patients with tPO2 <20 mm Hg (all p values <0.05). Conclusions: This is the first study to show a direct in vivo correlation between synovial tPO2, inflammation and cell migration, thus it is proposed that hypoxia is a possible primary driver of inflammatory processes in the arthritic joint.